Pengaruh PKB, PBB-P2, dan BPHTB terhadap PAD DK Jakarta periode 2019-2024 - Narti Eka Putri; Fandi Ahmad (IKRAITH-EKONOMIKA, 2025)
This study aims to determine: (1) the effect of Motor Vehicle Tax (PKB), (2) the effect of Rural and Urban Land and Building Tax (PBB-P2), (3) the effect of Duty on the Acquisition of Land and Building Rights (BPHTB), and (4) the combined effect of Motor Vehicle Tax (PKB), Rural and Urban Land and Building Tax (PBB-P2), and Duty on the Acquisition of Land and Building Rights (BPHTB) on Regional Original Revenue (PAD) of DKI Jakarta Province for the 2019–2024 period. This research is a quantitative study with a descriptive approach. The data used are secondary data in the form of reports on the realization of PKB, PBB-P2, BPHTB, and PAD revenues for the 2019–2024 period obtained from the Regional Revenue Agency (BAPENDA) of DKI Jakarta Province. The analytical method employed is multiple linear regression using SPSS version 26. The results show that partially, the Motor Vehicle Tax (PKB) has a significant effect on Regional Original Revenue (PAD). Meanwhile, the Rural and Urban Land and Building Tax (PBB-P2) and the Duty on the Acquisition of Land and Building Rights (BPHTB) do not have a significant effect on Regional Original Revenue (PAD). However, simultaneously, the results indicate that the Motor Vehicle Tax (PKB), Rural and Urban Land and Building Tax (PBB-P2), and Duty on the Acquisition of Land and Building Rights (BPHTB) together have a significant effect on Regional Original Revenue (PAD).